Потенціал стилістичної фрагментації в художньому тексті - Головащенко, Юлія Сергіївна; Боднарчук, Анастасія Русланівна (Гельветика, 2026)
The article explores the stylistic potential of syntactic fragmentation as a mechanism of affective encoding in contemporary literary discourse. Rather than treating syntax as a neutral vehicle of propositional meaning, the study adopts a stylistic perspective that foregrounds the role of grammatical organisation in the construction of literary sense. Drawing on theories of foregrounding, deviation, and sentence architecture, syntactic fragmentation is conceptualised as a stylistic strategy that deliberately deploys grammatically reduced or structurally disrupted constructions, including ellipsis, parataxis, minor sentences, clause suspension, and non-finite structures. The empirical focus of the study is Sally Rooney’s novel “Intermezzo”, selected for its recurrent use of non-canonical syntactic patterns at moments of heightened emotional tension. Through close qualitative analysis of selected passages, the article demonstrates how fragmented syntax functions as a structural encoding of affective states such as guilt, anxiety, emotional paralysis, and cognitive overload. Rather than naming emotions explicitly, the novel inscribes them into the grammatical fabric of narration, allowing affect to be enacted rather than described. The findings suggest that syntactic fragmentation operates as a central stylistic resource through which literary discourse produces experiential immediacy and emotional intensity beyond semantic content. By disrupting syntactic continuity, the narrative formalises emotional instability and registers internal conflict at the level of sentence structure. The study contributes to contemporary stylistics by theorising syntactic fragmentation as a distinct stylistic phenomenon and by demonstrating its sense-creating function in a contemporary novel. Future research may extend this framework to other genres, languages, and narrative traditions and may integrate corpus-based approaches to examine the distribution and stylistic salience of fragmented constructions across literary discourse
STYLISTIC POTENTIAL OF SYNTACTIC FRAGMENTATION IN LITERARY TEXT
Keywords: literary text; syntax; syntactic structure; sense vs. meaning; fragmentation; foregrounding